The Roles of Type I Interferon in Co-infections With Parasites and Viruses, Bacteria, or Other Parasites - Ma, Yuanlin; Su, Xin-zhuan; Lu, Fangli (Frontiers in Immunology, 2020)
Parasites, bacteria, and viruses pose serious health threats to public health. Many parasite infections, including infections of protozoa and helminths, can inhibit inflammatory responses and impact disease outcomes caused by viral, bacterial, or other parasitic infections. Type I interferon (IFN-I) has been recognized as an essential immune effector in host defense against various pathogens. In addition, IFN-I responses induced by co-infections with different pathogens may vary according to the host genetic background, immune status, and pathogen burden. However, there is only limited information on the roles of IFN-I in co-infections with parasites and viruses, bacteria, or other parasites. This review summarizes some recent findings on the roles of IFN-I in co-infections with parasites, including Leishmania spp., Plasmodium spp., Eimeria maxima, Heligmosomoides polygyrus, Brugia malayi, or Schistosoma mansoni, and viruses or bacteria and co-infections with different parasites (such as co-infection with Neospora caninum and Toxoplasma gondii, and co-infection with Plasmodium spp. and H. polygyrus). The potential mechanisms of host responses associated with co-infections, which may provide targets for immune intervention and therapies of the co-infections, are also discussed.